Cover Image, Volume 93, Issue 2. Issue 2 (5th January 2018) - Li, Jianfeng; Liu, Xinyuan; Wang, Shujun; Du, Zhiping; Guo, Yimin; Cheng, Fangqin
Abstract : The cover image, by Jianfeng Li et al., is based on the Research Article Synthesis and optimization of a novel poly‐silicic metal coagulant from coal gangue for tertiary‐treatment of coking wastewater, DOI:10.1002/jctb.5362 . Abstract : The cover image, by Jianfeng Li et al., is based on the Research Article Synthesis and optimization of a novel poly‐silicic metal coagulant from coal gangue for tertiary‐treatment of coking wastewater, DOI:10.1002/jctb.5362 .